Answer: OPTION B.
Explanation:
Given the following equation:
![10x - 25 - 3x = 4x- 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/szwyvjgyx42wa5ndwgamli3i8imu3yizun.png)
These are the steps to solve it:
Step 1
Add like terms on the left side of the equation:
![7x -25= 4x - 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vtdfntns8w55a0ym7j1xw5kfsy65lmze7a.png)
Step 2
Apply Addition property of equality, which states that:
![If\ a=b\ then\ a+c=b+c](https://img.qammunity.org/2020/formulas/mathematics/middle-school/htcg9p97dq0uci4f5r9pcvvfor3w46vw4a.png)
Then, we can add 25 to both sides of the equation:
![7x -25+(25)= 4x - 1+(25)\\\\7x=4x+24](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qc06hh1rkklponk5r7yv0lfdc4xlv1imq9.png)
Step 3
Applying the Subtraction property of equality, we can subtract
from both sides:
![7x-4x=4x+24-(4x)\\\\3x=24](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nqg4xb38x9jrgln067g43y0jos747x3qwk.png)
Step 4
Applying the Division property of equality, we can both sides of the equation by 3. Then:
![(3x)/(3)=(24)/(3)\\\\x=8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zzvvedock6i6e400sjrottkw1x3mxgmqx5.png)